Financial Literacy, Financial Attitude, and Household Financial Behavior - Jihan Zakiyah Permana; Lutfi Lutfi (Universitas Proklamasi 45, 2022)
Household financial behavior is a crucial topic to study because it determines the family's economic well-being. This study examines the effect of financial literacy, financial attitudes, financial experience, and income on household financial behavior. The object of this research is the family finance manager in Sidoarjo City, East Java. The data collection technique is using an online survey. Sample selection was done by using the purposive sampling technique. The sample of this research is 153 financial managers. The data analysis technique used the Partial Least Square Structural Equation Model (PLS_SEM). The results indicate that financial literacy and attitudes positively affect household financial behavior, while financial experience and income have no significant effect. This finding implies that financial policymakers should increase public financial literacy and attitude toward managing family finances.